Perlindungan Hukum Terhadap Pemegang Saham Minoritas Dalam Undang-Undang Perseroan Terbatas - Dwi Rahmawati; Bismar Nasution; Suhaidi Suhaidi; Mahmul Siregar (Iuris Studia: Jurnal Kajian Hukum, 2021)
The interests of minority shareholders in the company often conflict with a sense of justice and legal protection. This normative research discusses the issue of legal protection for minority public shareholders and the principle of justice in legal protection for minority shareholders. The legal protection of minority shareholders includes the right to propose a GMS (Article 79 paragraph 2 letter a), sue the board of directors (Article 97 paragraph 6) and the board of commissioners (Article 114 paragraph 6), request a company examination (Article 138 paragraph 3 letter a), and propose the dissolution of the company (Article 144 paragraph 1). The Company Law protects the rights of minority public shareholders based on the silent majority principle. The principle of justice to protect minority public shareholders is derived from the principle of distributive justice, the voting rights of minority shareholders are proportional to the portion of shares paid up, even though the equality is not equal. Judges' considerations regarding the legal protection of minority public shareholders are based on Article 138 paragraph (3) letter a of the Company Law, at least 1/10 of the total shares. Minority public shareholders are eligible to apply for an SLJ examination to the court. So that the minimum requirement of 1/10 of the total shares becomes a guideline to protect the rights of minority shareholders and as a derivation of the principle of distributive justice